Winter Wine Tourists in Canada's Niagara Region - Cullen, Carmen W. (Institutional Knowledge at Singapore Management University, 2006)
This paper represents the first stage in a multi-seasonal investigation of peak, off-peak and shoulder season winery tourists in Canada’s Niagara region. The goal of the study reported here is to better understand the off-peak winery tourist – that strange creature who chooses to visit a winery in the dead of Canadian winter. Who are these people?